(untitled) - Civitello, Linda (Hoboken, N.J., 2008)
Its purpose is to make your life easier: to further emphasize, organize, and explain information in the text and to help you plan lessons, give tests and learn even more about food history through links to web site.
Keywords: Food,Food,Thực phẩm,Thực phẩm; History,Social aspects,Lịch sử,Khía cạnh xã hội